1992
DOI: 10.1111/j.1574-6968.1992.tb05525.x
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory metabolism ofSaccharomyces cerevisiaein continuous culture

Abstract: Short‐period (40–50 min) synchronized metabolic oscillation was found in a continuous culture of yeast Saccharomyces cerevisiae under aerobic conditions at low‐dilution rates. During oscillation, many parameters changed cyclically, such as dissolved oxygen concentration, respiration rate, ethanol and acetate concentrations in the culture, glycogen, ATP, NADH, pyruvate and acetate concentrations in the cells. These changes were considered to be associated with glycogen metabolism. When glycogen was degraded, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(33 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Previously we have shown that many metabolites oscillate with a phase relationship to respiration (5,7,12). We expanded these data by using GC-MS to show that this oscillation is metabolome-wide (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previously we have shown that many metabolites oscillate with a phase relationship to respiration (5,7,12). We expanded these data by using GC-MS to show that this oscillation is metabolome-wide (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The metabolite data set used previous work (5,7,12,21,22,25,27,28,37,38), and GC-MS analyses (SI Methods) of intracellular metabolites were used to construct the metabolite data set. All Western blots were carried out according to the manufacturer's instructions (Atto, Bunkyo-ku, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter underscores the vital role of water associated with the ENOX1 proteinbound copper hexahydrate in the oscillatory process [31]. Among the first defined clock-related oscillation in yeast, known as the respiratory oscillation, was a 40 min cycle of dissolved oxygen levels in continuous culture [20][21][22][32][33][34][35]. After establishing that the oscillations were driven by some aspect of ethanol metabolism [33], acetaldehyde and sulfide were found to be responsible for synchronizing the cell population in continuous culture [22].…”
Section: Discussionmentioning
confidence: 99%
“…The strong feedback loop provides a good device for large amplitude fluctuations. Variations in cAMP level are known to occur upon glucose addition (Thevelein & Beullens, 1985), and have been reported during metabolic oscillations of cellular populations (Satroutdinov et al, 1992;Muller et al 2003). Oscillations in cAMP production might also be involved in the oscillatory shuttling of Msn2p in and out the nucleus (Jacquet et al, 2003).…”
Section: Discussionmentioning
confidence: 99%